THE EFFECTS OF OWNERSHIP STRUCTURE POST MERGER AND ACQUISITION ON BANKING PERFORMANCE IN INDONESIA - , Mohamad Rizky Hamami ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Recently, several banks developed merger and acquisition activities in Indonesian banking industries. With consideration of a change in the ownership of a bank, the development of merger and acquisition activities influence the performance of a bank. This is reasonable, since the owner of a bank has authority to control bank policy in the future. Therefore, it is interesting to examine the correlation between bank performance and ownership structure, post merger and acquisition activities in Indonesia. This study uses 459 observations of data from 32 banks that conducted mergers and acquisitions activities in Indonesia during the period of 2005-2010. This research finds that the relationship between ownership structure and performance of banks on Capital Adequacy Ratio, Non Performing Loan, Return On Asset and Operating Income Operating Expenses, is relatively low. Therefore, it can be concluded that there is less correlation between ownership structure and bank performance. The regression analysis also shows that the composition of ownership and number of ownership influence the performance bank on Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Return On Asset (ROA) and efficiency on Operating Income to Operating Expense (OIOE) significantly. In sum, this research illustrates that fundamental factors in the condition of the bank must be considered by owners and management of the bank in predicting the performance of banks postmerger and acquisitions. Therefore, Bank Indonesia as the regulator authority of banking and financial system in Indonesia needs to strengthen the system of banking supervision system and implement the regulation particularly with Merger, Acquisition and Consolidation.